2022
DOI: 10.1021/acs.chemmater.2c01866
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Templated Nanolines of Ru and RuO2 by Sequential Infiltration Synthesis

Abstract: Nanoscale patterning of inorganics is crucial for the fabrication of advanced electronic, photonic, and energy devices. The emerging sequential infiltration synthesis (SIS) method fabricates nanofeatures by block-selective vapor-phase growth in block copolymer templates with tunable patterns. Yet, SIS has been demonstrated mainly for Al2O3 and a few other metal oxides, while deriving metal nanostructures from a single SIS process is a challenge. Here, we present SIS of the Ru metal in polystyrene-block-polymet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Segal-Peretz et al have used SIS to grow AlO x inside the polar domains of PS- b -PMMA and drastically increase imaging contrast for TEMT in thin films. , We showed such contrast enhancement in BCP spheres by using ZnO x SIS in the PVP block of PS- b -PVP . While the stained block is most frequently the polar one, Poonkottil et al have also demonstrated growth of Ru or RuO 2 in PS by exposing PS- b -PMMA to a RuO 4 /H 2 or RuO 4 /methanol SIS process, respectively. As is the case with conventional vapor staining, it is also possible to stain triblock copolymers with SIS, as demonstrated by Shi et al…”
Section: (S)tem Tomographymentioning
confidence: 57%
See 1 more Smart Citation
“…Segal-Peretz et al have used SIS to grow AlO x inside the polar domains of PS- b -PMMA and drastically increase imaging contrast for TEMT in thin films. , We showed such contrast enhancement in BCP spheres by using ZnO x SIS in the PVP block of PS- b -PVP . While the stained block is most frequently the polar one, Poonkottil et al have also demonstrated growth of Ru or RuO 2 in PS by exposing PS- b -PMMA to a RuO 4 /H 2 or RuO 4 /methanol SIS process, respectively. As is the case with conventional vapor staining, it is also possible to stain triblock copolymers with SIS, as demonstrated by Shi et al…”
Section: (S)tem Tomographymentioning
confidence: 57%
“…38,93 We showed such contrast enhancement in BCP spheres by using ZnO x SIS in the PVP block of PS-b-PVP. 94 While the stained block is most frequently the polar one, Poonkottil et al 95 have also demonstrated growth of Ru or RuO 2 in PS by exposing PSb-PMMA to a RuO 4 /H 2 or RuO 4 /methanol SIS process, respectively. As is the case with conventional vapor staining, it is also possible to stain triblock copolymers with SIS, as demonstrated by Shi et al 96 TEMT is also important in characterizing BCP-templated metal oxide structures prepared by SIS after polymer removal.…”
Section: D Confinement (Spherical)mentioning
confidence: 99%
“…In contrast to top-down processes, the combination of bottom-up self-assembly of block copolymers (BCP) and selective deposition using sequential infiltration synthesis (SIS) (also named vapor phase infiltration (VPI)) offers a simple, cost-effective route for fabricating nanoscale periodic inorganic materials patterns, with feature dimensions ranging from 5 to 50 nm. , SIS, which is derived from atomic layer deposition (ALD), enables the growth of inorganic materials within polymers, converting them into hybrid organic–inorganic materials. , In SIS, the polymer is sequentially exposed to ALD precursors under conditions that promote diffusion into the polymer and interaction with it. Tuning process parameters such as diffusion time and number of growth cycles enables precise control over the spatial distribution and quantity of the grown inorganic materials within the polymeric volume. Since the growth of the inorganic material is also highly dependent on precursor–polymer interactions, the judicious choice of the polymer blocks that comprise a self-assembled BCP can yield selective growth in one of the blocks. Following the SIS process, the BCP film can be removed, resulting in an inorganic nanostructure, templated by the BCP morphology with high fidelity. , Indeed, SIS in BCP has been demonstrated as an efficient strategy for nanopattern fabrication with diverse applications such as semiconductor patterning, high-aspect-ratio structures for antireflective coatings, and isoporous ultrafiltration fabrication. …”
Section: Introductionmentioning
confidence: 99%
“…Up until now, various metal oxides and metals have been successfully synthesized via SIS, including AlO x , ,,, ZnO x , SiO x , TiO x , SnO x , VO x , GaO x , InO x , W, and Ru . Most of these metals and metal oxides have been grown directly in the polymer by favorable polymer–precursor interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation